Glycerol and biodiesel recovery from palm oil derived from used fried chicken cooking oil / Muhammad Hafiz Abdul Wahab - Abdul Wahab, Muhammad Hafiz (Faculty of Plantation and Agrotechnology, 2018)
This study is carried out to identify the percentage of glycerol and biodiesel in used fried chicken cooking oil and to provide the solution in recycling of used fried chicken cooking oil. The study was conducted using fried cooking “Sri Murni” vegetable oil brand with the objective to investigate the percentage of biodiesel and glycerol that can be produced from transesterification process. Moreover, new unused cooking oil of the same product will be used as control to find out the difference of biodiesel and glycerol before and after use. The crude glycerol is produced as the by-product from biodiesel has to be effectively utilized to solve environmental issues executed used cooking oil. In this study, the amount glycerol and biodiesel from fried chicken cooking oil of “Sri Murni” brand is better than those in plastic packaging. The volume of biodiesel in fried cooking “Sri Murni” vegetable are quite high which is around 400ml to 500ml in 800 ml and the volume of glycerol is around 35ml to 50ml as compared to fried cooking vegetable oil in plastic packaging that has quite low volume of biodiesel at around 200ml to 400ml. Moreover, the volume of glycerol is around 25ml to 35ml. Furthermore, the average 450mg of "Sri Murni" cooking oil with a total of 800ml beaker is 450ml / 800ml where 56.25% contains biodiesel and the average for glycerol is 4% from 800ml for a beaker. For cooking oil in plastic packaging, the average biodiesel is 40% and glycerol is 3.7%. From the result, there is a significant difference between the amounts of used fried chicken cooking oil, with the percentage amount of glycerol and Biodiesel in new, unused ones. Lastly, the difference of a biodiesel and glycerol depend on two types of fried cooking oils. The percentage of significance difference between fried cooking “Sri Murni” and plastic packaging are decrease in percentage after oil cooking were used. As a conclusion, the utilization of waste cooking oil is very important nowadays because raw materials are critically used in our country. Moreover, introduction of new technologies and cluster management system are essential for successful transformation of the utilization process.